Penerapan Model Pembelajaran Discovery Learning Pada Mata Pelajaran Creambath Di SMK Negeri 1 Buduran - novita nathania; Octaverina Kecvara Pritasari; Nia Kusstianti; Biyan Yesi Wilujeng (Program Studi Pendidikan Tata Rias, 2025)
The study's three main goals are to: (1) assess how well the discovery learning model syntax was implemented; (2) examine the learning outcomes of the students; and (3) gauge the reactions of the students to the application of the discovery learning model in the creambath class at SMK Negeri 1 Buduran. With its